The effect of sambiloto tablet (AS201-01) on placental Chondroitin Sulfate A (CSA) expression of pregnant mice infected by Plasmodium berghei - Nasrul Wahdi; Widjiati Widjiati; Aty Widyawaruyanti; Budi Prasetyo (Majalah Obstetri dan Ginekologi, 2018)
Objectives: To determine the effect of Sambiloto tablet (AS201-01) in reducing the placental Chondroitin Sulfate A (CSA) Expression of pregnant mice infected Plasmodiumberghei.Materials and Methods: Experimental study using 24 pregnant mice were divided into 4 groups with randomization. Uninfected group, the placebo group, the Sambiloto tablet (AS201-01) group and the DHP tablet (as a standart drug) group. The last three groups, were infected with P. bergheion day 9th of pregnancy, and the treatment was started at day 11th of pregnancy, and samples were terminated at day 15th of pregnancy by surgery. Placental sampling were stained with Tunnel assay to measure placental CSA antibodies.Results: The placental Chondroitin Sulfate A (CSA) expression. Uninfected group compared to Sambiloto tablet (AS201-01) groups was not significantly different (p>0.05), uninfected group compared with the other treatment groups differ meaningfully (p<0.05). Placebo group compared with all groups significantly different (p<0.05). Sambiloto tablet (AS201-01) group compared to uninfected group (p>0.05) was not significantly different, with another group was significantly different (p<0.05). DHP tablet group compared to all the groups was significantly different (p<0.05).Conclusion: Placental Chondroitin Sulfate A (CSA)expression of mice infected by Plasmodium berghei treated with Sambiloto tablet (AS201-01) lower than DHP tablet.